Establishing a South African Honour Society of Nursing under auspices of Sigma Theta Tau International (Inc.) - D. van der Wal (Curationis, 1998)
The information on Sigma Theta Tau International (Inc.) which follows is reproduced from official STTI documentation with permission from the STTI Chapter Manager. This section should thus be read with the United States context in mind as certain words and concepts have different meanings in the US and SA contexts, eg under graduate, graduate, college and the like. In addition, certain words are also spelled differently in American English and standard English.